Pengaruh Penyaluran Kredit PT. Bank SulutGo Cabang Tutuyan terhadap Pertumbuhan Ekonomi Daerah Kabupaten Bolaang Mongondow Timur - Aswin Paputungan; Mauna Th. B. Maramis; George M. V. Kawung (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Economic growth is one of the most important indicators in analyzing economic development that occurs in a country or region. Economic growth shows the extent to which economic activity will generate additional community income in a certain period. As is the case in many other regions in Indonesia, the financial sector, especially banking institutions, has a significant role in supporting the economic development process. One of the important instruments offered by banking institutions to encourage economic growth is the distribution of credit to the public and business world. This research aims to determine the partial and simultans influence of distribution of consumption credit, investment credit and working capital credit on regional economic growth in East Bolaang Mongondow Regency. The data used in this research is secondary data with an observation period of 10 years, namely 2014-2023, obtained from the Tutuyan branch of Bank SulutGO and the Central Statistics Agency of East Bolaang Mondondow Regency. The analytical method used in this research is multiple regression analysis. The results of the research show that the distribution of consumption credit has a positive and significant effect on regional economic growth, the distribution of investment credit has a positive and insignificant effect on regional economic growth, the distribution of working capital credit has a positive and insignificant effect on regional economic growth and together the distribution of consumption credit, investment credit and working capital credit influence regional economic growth in East Bolaang Mongondow Regency.